Work efficiency of office personnel Ta Phraya Subdistrict Administrative Organization, Ta Phraya District, Sa Kaeo Province - songnguan, sirawan (Journal of Modern business administration and management for Sustainable Development, 2024)
The purposes of this research are to 1) study the efficiency of work. Problems and obstacles affecting work performance Guidelines or methods for solving problems in work. 2) Guidelines, forms, methods for increasing the efficiency of work of personnel of the Ta Phraya Subdistrict Administrative Organization, Ta Phraya District, Sa Kaeo Province. It is qualitative research. Use document research and field research. by structured interview Sample groups include: Subdistrict employee management team, 24 hired employees, results The research results found that Efficiency in the work of personnel Mostly effective Personnel can perform their responsibilities successfully within the specified time period. The work that comes out is accurate and complete and the people are satisfied with the service. that can meet needs directly when compared to the output and results of operations that are more than inputs, problems and obstacles that affect operations areLack of personnel to perform duties Personnel still lack knowledge of regulations in performing their duties. Tools and equipment are insufficient and not up to date. There is a solution or method to solve the problem, which is to recruit additional personnel. and create awareness among personnel to love the organization Promote and support the development of knowledge about regulations in the performance of duties. Providing additional tools and equipment by means of rental and regular maintenance with guidelines, formats, and methods for increasing operational efficiency. There are suggestions as follows: 1) There should be free housing benefits for personnel as an incentive to work and transfer. 2) There should be a process for creating a material inspection plan. equipment tools for repairs and maintenance at least once a month; 3) there should be organized learning exchange activities in the organization of each work at least once a week; and 4) there should be organized activities to build relationships among personnel in the organization at least once a month.